TELECOMMUNICATIONS NETWORK THROUGH SIGNAL INJECTION POWER "POWER LINE COMMUNICATION" Network Connection INTERNET AS AN ALTERNATIVE - Yudi Irawan Chandra (JAKSTIK Journal, 2006)
The flow of electric current in a sinusoidal wave form apparently can be used for voice communication and data signals known as Powerline Communications (PLC). How is the concept?, In sederana this analogy that the electrical current can flow like water to generate waves and sea foam. Is the current wave, while the foam form of noise. Noise is utilized by the PLC technology to deliver voice and data signals.Â  Internet presence by some of our communities is a means of communication are quite expensive, so use only a limited circle only. One reason can we say, access the Internet through a telephone line which is very slow, it raises the amount of money should we spend. What's the solution? the answer is Digital Power Line technology.Â